PENERAPAN TEKNIK SELF MANAGEMENT UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS VIII SMP MUHAMMADIYAH 12 GKB GRESIK - Azzahra, Samda Awalia (Jurnal Psikologi Terapan, 2024)
This research aims to examine more deeply the effectiveness of self-management techniques in class VIII students who experience decreased motivation to learn. The data collection method used in this activity is collecting student learning motivation data using the questionnaire method as the main data, then observing and interviewing related parties. Observations are carried out by digging up information and observing students' conditions in classroom learning. From the results of interviews with several teachers and homeroom teachers, several categories of students were selected. Each class is represented by 6 students, namely classes VIII A, VIII B, VIII F. Based on the research results, it is known that students' low learning motivation can be increased after being provided with individual counseling services using Self Management techniques. The average student learning motivation is in the range of 50-60% which is included in the low category. Then, after implementing self-management techniques, there was an increase in learning motivation in the range of 70-85%. So it can be concluded that the application of individual counseling using Self Management techniques can be implemented effectively to increase student learning motivation